2011
DOI: 10.1186/1475-2840-10-106
|View full text |Cite
|
Sign up to set email alerts
|

Cardiometabolic risk variables in overweight and obese children: a worldwide comparison

Abstract: The growing prevalence rate of pediatric obesity, which is frequently accompanied by several cardiometabolic risk factors, has become a serious global health issue. To date, little is known regarding differences for cardiometabolic risk factors (prevalence and means) in children from different countries. In the present review, we aimed to provide a review for the available evidence regarding cardiometabolic risk factors in overweight pediatric populations. We therefore provided information with respect to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 34 publications
1
44
1
2
Order By: Relevance
“…The literature on the cause of hypertension describe a wide variety of genetic, metabolic, environmental, and socioeconomic influences on the development, severity, and comorbidities of hypertension. [28][29][30][31][32][33] Hypertension, in many, has multifactorial causes, and uric acid is one potential contributor that has varying impact depending on the population studied. Furthermore, this effect on BP is not isolated to those who meet criteria for hypertension, because adolescents with BPs in the prehypertensive range respond to urate-lowering therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on the cause of hypertension describe a wide variety of genetic, metabolic, environmental, and socioeconomic influences on the development, severity, and comorbidities of hypertension. [28][29][30][31][32][33] Hypertension, in many, has multifactorial causes, and uric acid is one potential contributor that has varying impact depending on the population studied. Furthermore, this effect on BP is not isolated to those who meet criteria for hypertension, because adolescents with BPs in the prehypertensive range respond to urate-lowering therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Those studies also showed that most of the children were sedentary [36,38]. The development of obesity secondary to genetic or excessive consumption of food has been proposed as a risk factor for developing metabolic alterations including insulin resistance and diabetes mellitus [39]. Transnational food chains have made energy-dense, low-cost food available and accessible to Mexican children in a community environment where food regulation is still scarce [40].…”
Section: Discussionmentioning
confidence: 99%
“…Childhood obesity has major implications on individual and population health [1,2] and on health care systems [3,4]. Yet, in many countries the prevalence is increasing [5,6].…”
Section: Introductionmentioning
confidence: 99%